ØªØ£Ø«ÙŠØ± Ø§Ù„ØªØ·Ø¨ÙŠÙ‚ Ø§Ù„ØªØ¹Ø§ÙˆÙ†ÙŠ Ù…Ù† Ù†ÙˆØ¹ÙŠØ© Ø§Ù„Ø¨Ø§Ù†ÙˆØ±Ø§Ù…Ø§ ÙÙŠ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ø¹Ù†Ø¯ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙØµÙ„ Ø§Ù„ØØ§Ø¯Ù‰ Ø¹Ø´Ø± Ø§Ù„Ø£ÙˆÙ„Ù‰ Ø¹Ù„ÙˆÙ… Ø§Ù„Ø¥Ø¬ØªÙ…Ø§Ø¹ÙŠØ© - Muhammad Dimyati; zuhrotul Mila (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2021)
Abstract Thepurpose of this study were (1) to determine the effectiveness and influence of the jigsaw cooperative learning model to improve the Arabic speaking skills of class XI IIS 1 MA Al Amiriyyah Blokagung Banyuwangi. This type of research is quantitative, by looking for the results of the group value which is given treatment with the control group. The approach used in this research is a quantitative approach because the data presented is related to numbers. The instrument used was a test instrument. Test data collection techniques and documentation. The data analysis technique is hypothesis testing.